Synthesis, crystal structure and optical properties of a new fluorocarbonate with an interesting sandwich-like structure. Issue 18 (25th April 2018) - Tang, Changcheng; Jiang, Xingxing; Guo, Shu; Xia, Mingjun; Liu, Lijuan; Wang, Xiaoyang; Lin, Zheshuai; Chen, Chuangtian
Abstract : A new fluorocarbonate, Na3 Zn2 (CO3 )3 F, was synthesized using a subcritical hydrothermal method. Abstract : A new fluorocarbonate, Na3 Zn2 (CO3 )3 F, was synthesized using a subcritical hydrothermal method. Na3 Zn2 (CO3 )3 F crystallizes in the space group C 2/ c with a sandwich-like framework in which the stacked [Zn(CO3 )]∞ layers are connected with one another by bridging F atoms and [CO3 ] groups alternately. Interestingly, each Zn atom is surrounded by one F atom and four O atoms, forming a distorted [ZnO4 F] trigonal bipyramid, which is observed for the first time in the carbonate system. Na3 Zn2 (CO3 )3 F has high transparency in a wide spectral region ranging from UV to mid IR with a short ultraviolet absorption edge (∼213 nm). First-principles calculations revealed that Na3 Zn2 (CO3 )3 F possesses a large birefringence (Δ n = 0.11, λ = 589 nm), which is mainly contributed by the coplanar arrangement of [CO3 ] groups in the ab plane. Na3 Zn2 (CO3 )3 F might find applications as a UV birefringence crystal.